2018
DOI: 10.1039/c8ra00985f
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis on the energetics, magnetism and electronic properties in a 45° ZnO grain boundary doped with Gd

Abstract: The structural stability and magnetic properties of a grain boundary (GB) formed by aligning two ZnO single crystals oriented at an angle of 45 is investigated by density functional theory, using generalized gradient approximation (GGA) and taking the U parameter into consideration for the 4f impurity states. We found that the GB is stable with no dangling bonds and inter-granular structures. The stability of defects such as Gd substituted to the Zn site (Gd Zn ), Zn vacancy (V Zn ) and O vacancy (V O ) as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Such ring patterns have been reported to form in supercells containing grain boundaries. [13][14][15]26,27] The Fe-Al bond length in the pristine GB is 2.48 A ˚, and in the relaxed structure, the bonds are readjusted such that Fe-Al distances vary from 2.3 to 2.6 A ˚. To study the probability of formation of native defects, vacancies are created at the GB by removing one Fe/Al atom at a time such that two different vacancy positions are created for both Fe and Al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such ring patterns have been reported to form in supercells containing grain boundaries. [13][14][15]26,27] The Fe-Al bond length in the pristine GB is 2.48 A ˚, and in the relaxed structure, the bonds are readjusted such that Fe-Al distances vary from 2.3 to 2.6 A ˚. To study the probability of formation of native defects, vacancies are created at the GB by removing one Fe/Al atom at a time such that two different vacancy positions are created for both Fe and Al.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Interfaces and GBs provide such available sites so that hydrogen can accumulate there, and extant research has shown that the presence of GBs in materials can significantly alter the properties and generate new physical phenomena. [12][13][14][15] Once hydrogen has accumulated at the FeAl GBs, it may reduce the cohesiveness of atoms leading to bond rupture and brittle fracture. [12] Attempts to enhance the ductility of the FeAl alloys have been made and include the formation of a protective oxide layer as well as introduction of ductility-enhancing elements such as Cr, B or C. [11] Vacancies are considered the simplest type of lattice defects, and GBs are the most common planar defects.…”
Section: Introductionmentioning
confidence: 99%
“…This process can be employed to analyze the temperature sensitivity and hopping type behaviors of grain and grain boundary in thermistors by analyzing their AC impedance spectroscopies at different temperatures [29]. Furthermore, researchers have confirmed that the appearance of grain boundary can change magnetic and electronic properties of semiconductors [30,31]. According to these different behaviors of grain and grain boundary, their characterizations can be strengthen and applied by changing their component proportion to meet the requirement of different applications.…”
Section: Introductionmentioning
confidence: 99%